Haploidentical Stem Cell Transplantation in Children With Hematological Malignancies Using αβ+ T-Cell Receptor and CD19+ Cell Depleted Grafts: High CD56dim/CD56bright NK Cell Ratio Early Following Transplantation Is Associated With Lower Relapse Incidence and Better Outcome - Diaz, Miguel A.; Zubicaray, Josune; Molina, Blanca; Abad, Lorea; Castillo, Ana; Sebastian, Elena; Galvez, Eva; Ruiz, Julia; Vicario, Jose Luis; Ramirez, Manuel; Sevilla, Julian; González-Vicent, Marta (Frontiers in Immunology, 2019)
We prospectively analyzed outcomes of haploidentical hematopoietic stem cell transplantation using T-cell receptor /CD19+ depleted grafts. Sixty-three transplantations were performed in 60 patients. Twenty-eight patients were diagnosed of ALL, 27 patients of AML and in 8 other hematological malignancies. At time of transplantation 23 were in first CR, 20 in second CR, 20 beyond second CR. Four patients developed graft failure. Among engrafted patients, the median time to neutrophil and platelet recovery was 14 (range 9–25) and 10 days (range 7–30), respectively. The probability of non-relapse mortality by day +100 after transplantation was 10 ± 4%. With a median follow-up of 28 months, the probability of relapse was 32 ± 6% and disease-free survival was 52 ± 6%. Immune reconstitution was leaded by NK cells. As such, a high CD56 dim/ CD56bright NK cell ratio early after transplantation was associated with better DFS (≥3.5; 77±8% vs <3.5; 28±5%; p=0.001) due to lower relapse incidence (≥3.5; 15±7% vs <3.5; 37±9%; p=0.04). T-cell reconstitution was delayed and associated with severe infections after transplant. Viral reactivation/disease and presence of VOD/SOS in the non-caucasian population had a significant impact on non-relapse mortality. TCR+ and CD19+ cell-depleted haploidentical transplant is associated with encouraging results especially in patients in early phase of disease. A rapid expansion of “mature” natural killer cells early after transplantation resulted on lower probability of relapse, suggesting a graft versus leukemia effect independent from graft-versus-host reactions.